Os limites estruturais do Supremo Tribunal Federal no Brasil: controle de constitucionalidade e medidas de exceção - Marques, Vitor (2020)
The matter under analysis in the present monograph is a historic and legal construction of constitutionalism in the east and its challenges and purposes over the centuries. In this order, it analyzed historic events, overall of the countries that had crucial participation on development of modern constitutionalism, in focus on England, France and United States of America. Besides the constitutionalism, its analyses the consequences and products of these processes derive from the relevance of judicial review. The analyses of judicial review, since its first days until today, justified by virtue of the claim of assessment on how occurred external influences, especially of United States of America on formation of control of constitutionality in Brazil. The Constitution of 1988 and the organization Judiciary Branch, mainly, of Supreme Court and how its structure to guarantee the protection of normative acts with efficiency and institutional evaluation. Apart from the challenge to control the Constitution from the vigilance of acts produced by Legislative and Executive Branches, the actual historical moment demands cautions of Judiciary so that will not be an source of exception acts. In other words, as well as supervise the acts against the federal Constitution, the Supreme Federal Court must cut off these exemption measures from Legislative and Executive powers. To achieve this purpose, it considered to elaborate another constitutional arrangement as one of the alternatives to reduce the production of exemption acts and a better way to protect the federal Constitution